Diagnóstico de la Calidad de Vida Laboral, Engagement y Burnout en Trabajadores de una Institución de Educación Superior (IES) en Ecuador - Armijo, Maria Isabel (2017)
During the last decades in Ecuador, the Institutions of Higher Education (IHE) have been involved in regulatory changes that force them to make adjustments in their structures affecting their personnel. The main objective of this article is to study the quality of working life, engagement and burnout among workers in the administrative and academic areas of an IHE. It begins with a review of the literature on the constructs of quality of work life, engagement and burnout, their definitions and main characteristics. Within an empirical study from 265 workers of an HEI that will determine their level of quality of life and identifies the dimensions that most contribute to their engagement. In the same way, the burnout is evaluated and the variables that most affect are presented. In general, it is concluded that there is a good level of engagement, a perception of a high quality of work life and a low level of burnout.